Civic Pedagogies in Higher Education
XI, 200 p.
Keywords: In this book, university teachers provide case studies illustrating methods employed to prepare citizens for meaningful participation in democracies, whether long-standing, young or emerging. Examples of practice from Western Europe, Eastern Europe, and North America are included, along with reflections and advice for practice.